Individual-level and plant-level predictors of acute, traumatic occupational injuries in a manufacturing cohort. Issue 7 (12th April 2014) - Souza, Kerry; Cantley, Linda F; Slade, Martin D; Eisen, Ellen A; Christiani, David; Cullen, Mark R
Abstract : Objectives: Workplace and contextual factors that may affect risk for worker injury are not well described. This study used results from an employee job satisfaction survey to construct aggregate indicators of the work environment and estimate the relative contribution of those factors to injury rates in a manufacturing cohort. Methods: Principal components analysis was used to construct four plant-level factors from responses to a 32 question survey of the entire workforce, administered in 2006. Multilevel Poisson regression was used to evaluate the relationship between injury rate, individual-level and plant-level risk factors, unionisation and plant type. Results: Plant-level 'work stress' (incident rate ratio (IRR)=0.50, 95% CI 0.28 to 0.90) was significant in the multilevel model, indicating the rate of injury for an average individual in that plant was halved (conditional on plant) when job stress decreased by a tertile. 'Overall satisfaction', 'work environment' and 'perception of supervisor' showed the same trend but were not significant. Unionisation was protective (IRR=0.40, 95% CI 0.17 to 0.95) as was any plant type compared with smelter. Conclusions: We demonstrated utility of data from a human resources survey to construct indicators of the work environment. Our research suggests that aspects of the work environment, particularly work stress and unionisation, may have a significant effect on risk for occupational injury, emphasising the need for further multilevel studies. Our work would suggest monitoring of employee perceptions of job stress and the possible inclusion of stress management as a component of risk reduction programmes.